PENGARUH PERTUMBUHAN TABUNGAN, DEPOSITO, DAN KREDIT TERHADAP PERTUMBUHAN PROFITABILITAS PADA PT BPR PARTAKENCANA TOHPATI DENPASAR - Mukarromah, Lailatul; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 4 No 8 (2015), 2015)
Bank Perkreditan Rakyat (BPR) is a bank whose role is to collecting and distributing fundS. The ability of the company making a profit is called profitability. Several factors need to be considered in order to achieve high profitability growth. The purpose of this study is to determine the significance of the effect of the growth of savings, deposits, and credit to the growth of profitability. The result of analysis showed that variable of savings and deposit growth is partially positive effect and not significant on the growth of profitability. Variable of credit growth is partially positive and significant effect on the growth of profitability.
Keywords: saving growth, deposit growth, credit growth, profitability